2021
DOI: 10.1097/meg.0000000000002055
|View full text |Cite
|
Sign up to set email alerts
|

Severity of liver test abnormalities in coronavirus disease 2019 depends on comorbidities and predicts early in-hospital mortality

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Patients infected with COVID-19 commonly experience LFT abnormalities [ 30 ]. Huang et al showed that patients with an AST level over three times the ULN (>3x ULN) had the greatest risk of mortality and artificial ventilation.…”
Section: Reviewmentioning
confidence: 99%
“…Patients infected with COVID-19 commonly experience LFT abnormalities [ 30 ]. Huang et al showed that patients with an AST level over three times the ULN (>3x ULN) had the greatest risk of mortality and artificial ventilation.…”
Section: Reviewmentioning
confidence: 99%
“…The worldwide figures of coronavirus disease 2019 (COVID-19) presently stand at 154640649 confirmed cases with 3232285 deaths[ 1 ]. Although primarily a respiratory syndrome, COVID-19 has been reported to cause liver injury in multiple studies, including metanalyses[ 2 - 4 ]. The incidence of liver injury as assessed by several indicators like transaminases, bilirubin and albumin has been found to be higher in patients with severe COVID-19 infection[ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of liver injury as assessed by several indicators like transaminases, bilirubin and albumin has been found to be higher in patients with severe COVID-19 infection[ 3 , 5 ]. Increasing severity of liver chemistry abnormalities on hospital admission predicts early in-hospital mortality in COVID-19 patients[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satapathy et al . demonstrated that liver chemistry abnormalities (LCA) including aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase and bilirubin were associated with the severity of COVID-19 [ 2 ]. Furthermore, LCA were linked to chronic liver disease but not with other risk factors of severe COVID-19, indicating chronic liver disease is an independent indicator of severe COVID-19.…”
mentioning
confidence: 99%